Influence of The Problem-Based Instruction (PBI) Model Based on Audiovisual Media Oon Students' Problem-Solving Skills and Cognitive Learning Outcomes - Susila Handayani; Herdiyana Fitriani (PAIDAGOGIA: Jurnal Inovasi Pendidikan dan Pembelajaran, 2024)
This study aims to describe the results of implementing PBI in Islamic Senior High School on students' learning outcomes and problem-solving abilities. The research adopts a Quasi-Experiment using a nonequivalent control group design. The subjects are tenth-grade students at Al-Aziziyah Islamic Senior High School, West Lombok, with classes XA and XC as the experimental and control groups. Students' problem-solving abilities are measured through assignments while learning outcomes are assessed using a 20-question multiple-choice and essay test. Data on students' problem-solving abilities are analyzed descriptively and categorized as follows: 80 ≤ Na ≤ 100 (very good), 60 ≤ Na ≤ 80 (good), 40 ≤ Na ≤ 60 (fair), 20 ≤ Na ≤ 40 (poor), and Na ≤ 20 (very poor). Students' learning outcomes data are analyzed using descriptive statistics, and a t-test is conducted to determine the difference in students' learning outcomes between the experimental and control groups. The research findings indicate that the audiovisual-based PBI model can enhance students' problem-solving abilities, supported by improving problem-solving abilities from the first to the second meetings in each experimental class. However, the influence of the audiovisual-based PBI model does not significantly impact the improvement of students' learning outcomes. This lack of influence is attributed to researchers' inability to plan, control, and condition the classroom. This results in suboptimal PBI syntax implementation and no significant improvement in students' learning outcomes in the experimental class.